The impact of ecological vulnerability on ecosystem service value and threshold identification: a case study of the Zhangjiakou-Chengde area, China - Wang, Ye; Xue, Zhong-cai; Yang, Yue; Ren, Wei; Ju, An-qi (Frontiers in Environmental Science, 2025)
IntroductionUnderstanding ecological vulnerability and its impact on ecosystem services is essential for promoting sustainable environmental management, particularly in ecologically fragile areas. This study focuses on the Zhangjiakou–Chengde area (ZC area), a representative ecologically sensitive area, and explores the mechanisms through which ecological vulnerability influences ecosystem service value.MethodsBased on the evaluation results of the ecosystem service value (ESV) and the ecological vulnerability index (EVI), this study employs Geodetector and constraint line analysis methods to examine their interrelationships.ResultsThe results indicate that: (1) from 2000 to 2020, there was a significant negative spatial correlation between ESV and EVI in the ZC area, with clusters of low ESV–high EVI in the west and high ESV–low EVI in the east; (2) among all the driving factors of EVI, fractional vegetation cover, land use intensity index, average annual precipitation, and population density were identified as the most influential factors on ESV. These variables exhibited clear threshold effects: ESV initially increased with the variable but began to decline after a certain threshold was exceeded; and (3) EVI itself also demonstrated threshold effects on ESV. In 2000 and 2010, ESV growth slowed and then turned negative once EVI exceeded 0.41 and 0.36, respectively. By 2020, EVI showed a consistently suppressive effect on ESV.DiscussionThese findings underscore the importance of identifying critical thresholds in ecosystem management to enhance the protection and sustainable improvement of ecosystem services in ecologically vulnerable areas.